We bought a zoo - Crowe, Cameron, 1957-; Yorn, Julie, 1969-; Yorn, Rick.; McKenna, Aline Brosh; Damon, Matt.; Johansson, Scarlett, 1984-; Church, Thomas Haden; Fugit, Patrick, 1982-; Fanning, Elle, 1998-; Higgins, John Michael; Mee, Benjamin; LBI Entertainment (Firm); et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2012)
A memoir by Benjamin Mee, tells the true account of how the author and his family used their life savings to buy a dilapidated zoo, replete with 200 exotic animals facing destruction, in the English countryside. Mee, along with his children, had to balance caring for his wife, who was dying of brain cancer, with dealing with escaped tigers, raising endangered animals, working with an eclectic skeleton crew and readying the zoo for a reopening.
DVD, NTSC, region 1; widescreen (1.85:1) presentation; Dolby Digital 5.1 (English), Dolby surround (French, Spanish).
English subtitles for the deaf and hard of hearing (SDH); English descriptive audio for people with visual disabilities; closed-captioned.
English, French or Spanish dialogue with optional Spanish subtitles.
Title from container.
Matt Damon, Scarlett Johansson, Thomas Haden Church, Patrick Fugit, Elle Fanning, John Michael Higgins.
Music by Jonsi; film editor, Mark Livolsi.
Keywords: Zoos -- England -- Drama; Zoo directors -- England -- Drama; Brain -- Tumors -- Patients -- Drama; Zoológicos -- Inglaterra -- Teatro; Feature films; Comedy films; Biographical films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities